The Role of Islamic Education Teachers in Shaping Students' Religious Character at SDIT Mutiara Rahmah - Aghnina, Dian; Lukman, Syaiful (Journal of Educational Research and Practice, 2023)
Education is not only about educating students to become intelligent individuals, but also about shaping their personalities to possess noble manners. Consequently, Islamic Religious Education instructors play a pivotal role in shaping the religious identities of their pupils. The purpose of this study is to learn how the Islamic Religious Education instructors at SDIT Mutiara Rahmah Balikpapan influence their students' religious identities. Qualitative research with a field research technique is the methodology used. Data collection techniques include observation, interviews, and documentation, followed by analysis and conclusions drawn from the obtained data. Based on the research results: 1) The role of Islamic Religious Education teachers in shaping students' religious characters at SDIT Mutiara Rahmah Balikpapan is carried out by setting an example and being a role model for their students. Additionally, the formation of religious characters is achieved through the habituation of engaging in religious activities at school. Islamic Religious Education teachers also play roles as motivators, guides, educators, and evaluators. 2) Islamic religious education instructors shape their pupils' religious personalities by making them habitually participate in religious activities. 3) The religious character of fourth-grade students is generally good, evident from their habitual engagement in religious activities at school. However, there are still some students who need to be reminded or guided.